PENGARUH TARIF DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PENUMPANG DALAM MEMILIH JASA TRANSPORTASI PO. SUMBER ALAM - Budi Fermansah; Hari Susanta Nugraha; Widiartanto Widiartanto (Universitas Diponegoro, 2015)
PO. Sumber Alam is a private company in the field of transport services are in Kutoarjo. The role of PO. Sumber Alam are very important in helping people who will be traveling to Jakarta or Yogja. PO. Sumber Alam is committed to serve passengers as well as possible so that passengers feel satisfaction with the services toward PO Sumber Alam. The study was conducted in the PO. Sumber Alam Kutoarjo on passenger buses sumber alam Jakarta to Yogyakarta. Based on data obtained it can be seen that in January 2013-March 2014 the last passenger quota provided by the PO. Sumber Alam are not fully charged. This study aims to determine the effect of fare and quality of service to passengers decision in choosing transportation services PO. Sumber Alam. The sample size in this study is as many as 100 respondents were obtained by using the formula Slovin with the characteristics of the selected respondents had used the Sumber Alam bus service at least twice. The sampling technique used was purposive sampling. The primary data obtained from the questionnaire that has been proposed to obtain a complete picture of what is needed. The analysis in this study is known by calculation software applications (software) SPSS 16 for Windows where the process and results of data analysis as a unit step in hypothesis testing.